Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.33549/physiolres.933328
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Values of Cardiovascular and Respiratory Parameters Predict Response to Acute Hypoxia in Young Healthy Men

Abstract: The majority of the available works have studied distinct hypoxic responses of respiratory and cardiovascular systems. This study examines how these systems interact while responding to hypoxia and whether baseline metrics moderate reactions to a hypoxic challenge. Central hemodynamic, aortic wave reflection, and gas exchange parameters were measured in 27 trained young men before and after 10-min normobaric isocapnic hypoxia (10 % O2). Associations were assessed by correlation and multiple regression analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 50 publications
(31 reference statements)
0
10
0
1
Order By: Relevance
“…The reduced availability of O 2 and CO 2 would increase the heart rate and blood pressure exponentially even at low workloads. This physiological alteration may increase aortic pressure and left ventricular pressures, leading to an upsurge of cardiac overload and coronary demand [22]. Further increased respiratory load against the "valve breathing", leads to increased respiratory muscle load and pulmonary artery pressure, in turn, adding to the cardiac overload.…”
Section: Increased Cardiorespiratory Stressmentioning
confidence: 99%
“…The reduced availability of O 2 and CO 2 would increase the heart rate and blood pressure exponentially even at low workloads. This physiological alteration may increase aortic pressure and left ventricular pressures, leading to an upsurge of cardiac overload and coronary demand [22]. Further increased respiratory load against the "valve breathing", leads to increased respiratory muscle load and pulmonary artery pressure, in turn, adding to the cardiac overload.…”
Section: Increased Cardiorespiratory Stressmentioning
confidence: 99%
“…It has been shown earlier in our laboratory (Divert et al, 2015) that cardiorespiratory reactions to hypoxic and hypercapnic tests divide athletes into the clusters depending on the type of sports performance they are specialized in. This finding has initiated subsequent studies that led to the conclusion of a close, mutually substitutional relationship between respiratory and cardiovascular systems under hypoxic conditions (Melnikov et al, 2017). For example, it has been shown that the parameters of the training process and the features of the respiration pattern that appear as a consequence of training modulate the sensitivity of brain structures to hypoxia as reflected in changes in the EEG α-rhythm under conditions of hypoxia (Balioz and Krivoshchekov, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…After 42 days of CIHH treatment, animals were placed into a custom‐made, closed container where they received a ten‐minute acute normobaric hypoxia (10% O 2 ). Electrocardiograms of conscious rats were continuously recorded before (normal oxygen), during (hypoxia), and after hypoxia (reoxygenation).…”
Section: Methodsmentioning
confidence: 99%